Management Of Strengthening Character Education In Fostering Morals Of Karimah Students At Madrasah Tsanawiyah, Bandung Regency - Arifin, Furqon; Ulfiah, Ulfiah; Sauri, Supyan; Koswara, Nandang (International Journal of Educational Research & Social Sciences, 2022)
This research is motivated by the thought of developing character education, especially in the world of education as a strategic step for the sustainability and excellence of the nation in the future. The world of education is a world that is expected to shape the character of the young generation of the Indonesian nation, considering that character education is the main priority in the educational goals of the current government. In accordance with the reference to President Joko Widodo's vision, namely carrying out a "Mental Revolution" through the policies contained in the Presidential Regulation of the Republic of Indonesia No. 87 of 2017 concerning Strengthening Character Education. However, some student phenomena are found, for example not doing homework, cheating, skipping school without permission, or being indifferent to cleanliness in the school environment, fights between students, bullying, brawl and lazy to study. It is hoped that with character education programs in madrasas based on Islamic boarding schools, students can participate in character education planting activities, one of which is activities in Islamic boarding schools. This study aims to determine and analyze: (1) Planning, (2) Organizing, (3) Implementation, (4) Evaluation, (5) Character education results, (6) Barriers and carrying capacity, (7) Solutions to overcome obstacles. There are three foundations in this research, covering theological, philosophical and six value systems. The theory that underlies this research is management theory and quality theory. This research uses a qualitative approach with a case study method. Data was collected by using triangulation techniques using interviews, document studies, and field observations. With the research subject, the head of the boarding school, the head of the madrasa, teachers and students. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. As for the conclusions of the research results, in general, the management of character education in the development of noble character, students of the Boarding School program at Madrasas at Al-Jawahir Islamic Boarding School and Al-Ihsan Islamic Boarding School, are oriented to the vision, mission and goals that must be realized at a certain time through analysis. resources owned by the school, both human resources and other resources, so that the achievement of school goals can be realized.